Anatomic Variation of the Lateral Sinus in Patients With Idiopathic Intracranial Hypertension: Delineation With Black-Blood Contrast-Enhanced MRI - Tian, Yu; Zhang, Zhe; Jing, Jing; Dong, Kehui; Mo, Dapeng; Wang, Yilong (Frontiers in Neurology, 2021)
Objectives: The purpose of this study was to describe the peculiar anatomic variations in the lateral sinuses and analyze the patterns of cerebrospinal fluid(CSF) drainage by using high-resolution black-blood contrast-enhanced magnetic resonance imaging(HRBB-enhanced MRI) in patients with IIH. Methods: Total 33 IIH patients who were found CVSS by MR venography (MRV) were enrolled in the study. HRBB-enhanced MRI was used to assess anatomical variational features of the transverse sinus and sigmoid sinus. The development of bilateral sinuses was first evaluated, including unilateral hypoplasia with contralateral dominance or bilateral balanced development. Then, four kinds of anatomical variations were eventually recorded, including circumscribed stenosis, arachnoid granulation (AG), fibrous septum (FS), and brain herniation (BH) into DVS. Results: Bilateral venous drainage dysfunction was found in 30(90.9%) patients, whereas only 3(9.1%) patients presented unilateral venous drainage dysfunction. The most common case is hypoplasia in unilateral sinus combined with anatomic variation in the contralateral dominant transverse sinus such as AG, BH into DVSs. Total of 52 anatomic variations were finally found in bilateral transverse sinuses in 33 enrolled patients, including 19(36.5%)AGs, 12(23.1%)FS, 7(13.5%) BH into DVS and 14(26.9%) circumscribed stenoses. Moreover, 41(62.1%) lateral sinuses showed enhancement in T1-weight-enhanced MRI. Conclusions: Patients with CVSS almost had CSF outflow disorders, whatever bilateral equalization or unilateral hypoplasia with contralateral dominance. Four main anatomic forms of obstruction caused venous reflux disorder by elevating the intracranial press, including circumscribed stenosis, hypoplasia, AG, FS, and BH into DVS.